Child and adolescent mental health services in Aotearoa New Zealand - Edward Miller; Anthony James (BJPsych International)
This paper aims to give an overview of child and adolescent mental health services (CAMHS) in Aotearoa New Zealand. We provide a brief overview of the demographics of the country and include the most up-to-date epidemiological data on child and adolescent mental health. To meet these psychiatric needs, we consider the present workforce, governance, funding and structure of CAMHS. Current psychiatric practice is heavily influenced by the country's unique history and cultural mix. Aotearoa New Zealand is noted for outstanding epidemiological research.